Global Attractors in H1(ℝN) for Nonclassical Diffusion Equations - Qiao-zhen Ma; Yong-feng Liu; Fang-hong Zhang (Discrete Dynamics in Nature and Society)
We study the existence of global attractors for nonclassical diffusion equations in H1(ℝN). The nonlinearity satisfies the arbitrary order polynomial growth conditions.